(3JaQjX hJYdjb Ydi QSGdI GdecjfI aj GdcjfI cjfIs
(3ChdgG (B:s
(3GdMeO ddg GdPj ChOY GdCSQGQ GdcejI aj LhgQI ef CQV GdNehd hGdScjfI hHYO abO hbaJ Ydi gPg GdQSGdI hCLdHJ GdfXQ ajgG hJJHYJgG ebGdI ebGdI s
(3BNQgG (B:s
(3HLGg SbjY GdNdb hPj GdfhQ hGdHgGA s
(3Vef eLehY , JQJjHgG (B: 11s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs